Sams teach yourself Facebook in 10 minutes - Gunter, Sherry Kinkoph (Sams Pub., 2011)
Sams Teach Yourself Facebook® in 10 Minutes , Second Edition offers straightforward, practical answers when you need fast results. By working through 10-minute lessons, you'll learn everything you need to know to quickly and easily get up to speed with Facebook. Tips point out shortcuts and solutions Cautions help you avoid common pitfalls Notes provide additional information 10 minutes is all you need to learn how to… Start a new account and build a profile page Connect with friends, coworkers, and family members Post status updates, comments, and view news feeds Communicate through Wall posts, messages, and live chat Create a blog with Facebook notes Share photos, videos, and favorite links Add applications to enhance your Facebook experience Share a hobby or interest using Facebook groups Keep track of upcoming events and happenings Create an official Page for a band, business, or other organization Keep connected with Facebook through your mobile device Control your privacy settings and keep your information safe.